Centrifugally cast ( spun ) iron pipes for water, gas & sewage - British Standards Institution (London BSI, 1945)
Cast-iron pipelines, Pressure pipes, Pipes, Cast-iron, Water, Gas pipes, Sewage, Sewerage, Test specimens, Sampling methods, Hydraulic tests, Testing conditions, Tensile testing, Pipe coatings, Marking, Tensile strength, Hardness, Spigot-and-socket joints, Thickness, Diameter, Weight (mass), Test equipment, Dimensions
Revised, Withdrawn
Replaced by BS 1211:1958
Keywords: Iron pipes -- Standards